Successful Treatment with Bosentan of Lower Extremity Ulcers in a Scleroderma Patient - Alix Naert; Petra De Haes (Case Reports in Medicine)
Digital ulcers are a well-known problem in patients with systemic sclerosis. Lower extremity ulcers are less prevalent but are also a challenging and underestimated complication of the disease causing important pain and morbidity. Bosentan, an oral dual endothelin receptor antagonist, has been shown to be effective in preventing digital ulcers in patients with systemic sclerosis. A few recent observations showed the efficacy of bosentan for accelerating the healing of nondigital ulcers in scleroderma patients. This report deals with a 48-year-old patient with systemic sclerosis who developed painful ulcers on the left ankle and hallux. The ulcers were refractory to a combination of vasodilator therapy with a calcium antagonist and several courses of intravenous prostanoids, low molecular weight heparin, aspirin, simvastatin, and intensive local treatment. Bosentan treatment showed spectacular healing of the ulcers already after 4 months of therapy. This case supports the previous few observations of accelerating wound healing of lower extremity ulcers in systemic sclerosis patients with bosentan treatment.